O conhecimento linguístico em materiais de espanhol publicados na década de 1940: análise historiográfica da primeira gramatização massiva dessa língua estrangeira no Brasil - Alexandre, Diego José Alves (2021)
This thesis aims to investigate the linguistic knowledge in Spanish teaching materials published in Brazil during the 1940s from theoretical and methodological bases of the Historiography of Linguistics, whose scientific activities focus on the set of events, facts and processes of conceptualization and description that constituted linguistic thought and practices over time (SWIGGERS, 2009). Therefore, it starts from two hypotheses: a) that these linguistic instruments, the result of educational policies of the time in question, because they had their genesis in a fertile period of studies on language in Brazil, therefore reflected this effervescence theoretical; b) that, considering the limited supply of Spanish materials in the period, the authors of the analyzed works were also based on theoretical discussions around the Portuguese language, which would influence some of the statements contained in these books. Thus, in order to promote the historiographical reconstruction of Spanish in Brazil in the first half of the twentieth century, three “Research Traditions” (LAUDAN, 2011 [1978]) that, at the time, disputed the academic-institutional space and curricular: Philology, Linguistics and Grammar. In addition, the historical context of Brasil República and its relationship with the educational-editorial system were also observed, in an effort to link the Secondary Education Reform of 1942, which established Spanish as a school discipline, the ministerial ordinance 127/1943, signed during the government of Getúlio Vargas, which fixed the Spanish-language content to be studied in Brazilian schools, to the first massive grammatization of Spanish as a foreign language in Brazil. After six sources were selected – Pozo y Pozo (1943), Solana and Morais (1944), Jucá Filho (1944), Becker (1945), Hernández (1946) and Barros (1948) –, these were analyzed based on the Layers of knowledge linguistic (SWIGGERS, 2004) – contextual, theoretical, technical and documentary layers . In the contextual layer, the relationship between linguistic and educational policies of the first decades of the Republic and the constitution of theoretical, methodological and didactic models in Brazil, notably marked by the strength of the grammatical tradition. In the theoretical layer, it was possible to verify the notion of Spanish language that underpinned the works, as well as the argument of influence (KOERNER, 2014), present in the authors' statements. In the technical layer, the analytical eye was fixed on the grammatical-terminological organization of each author, their metalinguistic presentation strategies and their theoretical (dis) agreements. In turn, in the documentary layer, it was observed a wide range of authors, literary and theoretical, used in the sources to give authority to the concepts and examples linked to Spanish grammar published on Brazilian territory. In the final remarks, it was noticed that in the Spanish materials published in Brazil during the fertile 1940s, although theoretically and methodologically similar to normative grammars, there was also a small space for linguistic reflection, especially with regard to variation, notions right/wrong, and the conceptual/terminological disagreement between the authors, a fact that confirms the initial hypothesis of the thesis. It was also found that, in addition to the potential influence of the grammar of Andrés Bello and the Royal Spanish Academy, the Portuguese grammars influenced the elaboration of part of these Spanish materials, thus consolidating a “contrasting practice” in the teaching of Castilian in Brazil. Finally, the linguistic knowledge of Spanish materials of the 1940s is characterized from three aspects: the conceptual, the grammatical and the documentary.